A back extrusion test for evaluating cooked rice texture - Kittichai Banjong; Jindal, Vinod Kumar; Illangantileke, Sarath G.; Gupta, Chandra P.; US/ASEAN (Bangkok : Asian Institute of Technology, 1986)
The hardness values of 5 different varieties of raw and parboiled rice cooked to 68 % moisture content ( wb) were measured using various back extrusion test cells and compared with the modified OTMS method. The selected rice samples representd non waxy rice of different amylose types. The back extrusion tests appeared to be more sensitive than the OTMS and were equa ll y reproducible. In addition , They were simpler , easy to perform and inexpensive in comp arison with the OTMS method. The correlation coefficients between h ardness values and physicochemical properties for both back extrusion and the OTMS met hod s were almost identical. In particular , a very high correlation between hardness and amylose content existed in both the methods. Among the different back extrusion cells tested for evaluating the texture of cooked rice samples a spherical plunger having 1 mm annulus width in a 30. 9 mm dia stainless steel cylinder produced best results
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1986
Keywords: Rice; Food texture